FORMATION OF NON-STANDARD THINKING IN THE LESSONS OF MATHEMATICS IN JUNIOR SCHOOLCHILDREN (American Journal of Pedagogical and Educational Research, 2022)
The article is devoted to an important and significant topic for primary general education - the formation of non-standard thinking in mathematics lessons for younger students. Approaches to the formation of creative thinking of primary school students are analyzed, the main types of non-standard arithmetic problems are described, and solutions to these issues are given.